Wear Mechanism of Multilayer AlCrWN/AlCrWSiN-coatings on Cemented Carbide Tools Prepared by Arc Ion Plating in Dry Cutting of Hardened Sintered Steel - Wada Tadahiro; Hanyu Hiroyuki (MATEC Web of Conferences, 2019)
In this study, to clarify the wear mechanism of the multilayer AlCrWN/AlCrWSiN-coated tool in cutting of hardened sintered steel, the rate of wear in the cutting of hardened sintered steel using three types of coated tools was investigated. The Type I tool had a single layer (Al60, Cr25, W15)N coating film, the Type II tool had a single layer (Al53, Cr23, W14, Si10)N coating film and the Type III tool had a multilayer (Al60, Cr25, W15)N/(Al53, Cr23, W14, Si10)N-coating film. Scanning electron microscope (SEM) observation and electron dispersive X-ray spectrometry (EDS) mapping analysis of the abraded surface of the coating film were performed. The following results were obtained: 1) The wear rate of the Type III tool was the slowest. 2) The area of the worn surface on the rake face “S” and the contact length between the rake face and the chip “D” were measured. Comparing the three types of coated tools, both the “S” and the “D” of Type I tool were the smallest, and those of Type II tool were the largest. 3) The main wear mechanism of Type II and Type III tool showed abrasive wear. However, the main wear mechanism of the Type I tool was both abrasive wear and adhesion wear. 4) The critical scratch load of the Type I tool, 81 N, was lower than that of the Type II or the Type III tool, over 130 N. Therefore, comparing the Type I and Type III tools, due to the wear mechanism of the Type 1 tool being both abrasive wear and adhesion wear, the wear rate of the Type I tool, which has the lower critical scratch load, was slower.